2014
DOI: 10.1097/sa.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Albumin 5%, Hydroxyethyl Starch 130/0.4 6%, and Ringer’s Lactate on Blood Loss and Coagulation After Cardiac Surgery

Abstract: T he optimal perioperative fluid management regimen for patients having major surgery is still being debated. Crystalloids (eg, Ringer's lactate [RL]), and colloids such as hydroxyethyl starch (HES) and 5% human serum albumin (HA) are used for intraoperative fluid management in patients undergoing cardiac surgery. The latter 2 expand circulating volume to a greater extent than crystalloids and could be used for a restrictive fluid therapy regimen. Human serum albumin and HES, however, can affect blood coagulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 3 publications
2
30
2
1
Order By: Relevance
“…of number of platelets) remained within reference laboratory values. These results are in line with previous investigations showing that crystalloids have less effect on blood coagulation compared to colloids [10]. Contrary to a few other studies, we revealed that platelet function was not affected by the study solutions.…”
Section: Resultscontrasting
confidence: 52%
“…of number of platelets) remained within reference laboratory values. These results are in line with previous investigations showing that crystalloids have less effect on blood coagulation compared to colloids [10]. Contrary to a few other studies, we revealed that platelet function was not affected by the study solutions.…”
Section: Resultscontrasting
confidence: 52%
“…In addition, more patients returned to the OR for bleeding during the period when albumin was used more often. These findings may suggest that the bleeding risk may be less when albumin is avoided, as albumin has been shown to negatively affect the coagulation cascade and lead to more bleeding in cardiac surgery patients …”
Section: Discussionmentioning
confidence: 99%
“…There has recently been concern regarding the use of HES infusions in surgical patients, and HES has been universally accepted to be contra-indicated in patients with sepsis, burn injuries or critical illness [31]. In addition, HES is known to interfere with blood coagulation [32,33]. However, it has been reported that surgical patients did not suffer adverse renal effects, increased blood loss, more transfusion, or increased mortality in response to intra-operative HES administration [34].…”
Section: Discussionmentioning
confidence: 99%